Credibilistic programming : an introduction to models and applications - Li, Xiang (Uncertainty and Operations Research, 2013)
It provides fuzzy programming approach to solve real-life decision problems in fuzzy environment. Within the framework of credibility theory, it provides a self-contained, comprehensive and up-to-date presentation of fuzzy programming models, algorithms and applications in portfolio analysis.